Pengaruh Pemberian Nugget Ikan Terbang Asap Dan Ikan Terbang Segar Terhadap Balita Underweight Usia 24-59 Bulan Di Desa Tallu Banua Sendana - Jamal, Nur Afika; Aryanti, Novi; Muzakkir (Nutrition Science and Health Research, 2025)
Background: Underweight is a lack of energy and nutrients needed according to age. Children's nutritional status can be affected by two things, namely insufficient food intake and infectious diseases. The purpose of this study was to determine the effect of giving smoked flying fish nuggets and fresh flying fish nuggets on underweight toddlers. This study is a type of experimental Quasi research with a pre-test and post-test nonequivalent control group design. Sample selection uses the Slovin formula. The research sample was underweight toddlers aged 24-59 months in Tallu Banua Village, Sendana District, Majene Regency who met the inclusion criteria. The number of samples was 38 toddlers, 19 people for the fresh flying fish nugget intervention group and 19 people for the smoked flying fish nugget intervention group. The results showed that the average weight gain was 1.6 kg when given fresh flying fish nuggets and the average weight gain was 1.4 kg when given smoked flying fish nuggets. Conclusion: fresh and smoked flying fish nuggets had a significant effect on underweight toddlers in the Tallu Banua Village area (p=0.000). The next researcher suggestion is expected to conduct more in-depth research related to the Effect of Giving Flying Fish Nuggets on the Weight of Toddlers.